2008
DOI: 10.1017/s0007114508159001
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate seed oil consumption during a period of high-fat feeding reduces weight gain and reduces type 2 diabetes risk in CD-1 mice

Abstract: The health benefits of pomegranate consumption have recently received considerable scientific focus, with most studies examining fruit and/or juice consumption. Pomegranate seed oil (POMo) is a rich source of 9-cis, 11-trans conjugate linolenic acid (CLA), which may offset the side-effects associated with weight gain. Male, wild-type CD-1 mice were divided into one of three groups (twenty per group): high-fat (HF), HF þ seed oil (HF þ POMo) or lean control (LN). In HF and HF þ POMo, mice were provided access a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 28 publications
6
84
0
3
Order By: Relevance
“…Up-regulation of PPAR-γ responsive genes by PA may be a mechanism of PSO-induced increase in serum insulin 79 . Anti-diabetic and insulin sensitizing effects of α-linolenic acid were also reported in other studies 53,[78][79][80][81] .…”
Section: Effects On Insulin Resistancesupporting
confidence: 73%
See 1 more Smart Citation
“…Up-regulation of PPAR-γ responsive genes by PA may be a mechanism of PSO-induced increase in serum insulin 79 . Anti-diabetic and insulin sensitizing effects of α-linolenic acid were also reported in other studies 53,[78][79][80][81] .…”
Section: Effects On Insulin Resistancesupporting
confidence: 73%
“…Insulin sensitivity was improved with 61.79mg/day PSO in mice which was treated with rich fat regimen compared to control group. In addition, final body weight, body weight accumulation, serum adiponectin, serum leptin, and serum insulin were reduced in treated group 78 .…”
Section: Effects On Insulin Resistancementioning
confidence: 89%
“…It was stated that PSO reduced body weight gain, and leptin and insulin levels in pathogen-free mice (McFarlin et al, 2009). It was also observed that PSO supplementation in diet improves glucose tolerance and suppresses obesity related inflammation (Hontecillas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations suggest that oral administration of PSO to mice with dietary PSO improved insulin resistance and high-fat-diet-induced obesity [38,39] . Vroegrijk et al also showed that body weights were decreased by reducing fat mass in PSO fed animals during 12 w. But they did not find insulin concentration or a lower fasted glucose in these animals [38] .…”
Section: Pa and Diabetes Mellitusmentioning
confidence: 99%